Math Questions and Answers

Start Your Free Trial

`y = 2x - 5, y = 5x - 11` Use any method to solve the system.

Expert Answers info

Borys Shumyatskiy eNotes educator | Certified Educator

calendarEducator since 2015

write1,102 answers

starTop subjects are Math and Science

Use the substitution method: substitute `y=2x-5` into the second equation and obtain

`2x-5=5x-11,` or

`3x=6,` or `x=2.`

Therefore `y=2x-5=-1.`

The answer: `x=2,` `y=-1.`

check Approved by eNotes Editorial



loves2learn | Student

Rearrange the equations to Ax+By=C form:

`-2x+y=-5`

`-5x+y-11`

 

Multiply first equation by -1.

After multiplying we have the following system:
`2x-y=5`

`-5x+y=-11`

 add the two equations together to eliminate y from the system.
`-3x=-6`

find x
`x=2`

substitute the value for x into the original equation to solve for y.
`-2(2)+y=-5`
`y=-1`

Therefore, `x=2 and y=-1`